Prison pedagogies: learning and teaching with imprisoned writers - Lockard, Joe; Rankins-Robertson, Sherry (Syracuse University Press, 2018)
Introduction: prison writing in a dark time / Joe Lockard and Sherry Rankins-Robertson -- Free writing and unfree writers -- Prison writing education and us working-class consciousness / Joe Lockard -- Wordsuncaged : a dialogical approach to empowering voices / Bidhan Chandra Roy -- Prison writing : creating literature and community organization / Juan Pablo Parchuc -- Freedom within limits : the pen(cil) is mightier / Ashwin J. Manthripragada -- Something other than progress : indigenous methodologies and higher education in prison / Anna Plemons -- Jail and juvenile-hall writing -- Curating counternarratives beyond bars : speaking out with writers at a county jail / Tobi Jacobi -- Writing with incarcerated teen women : trauma-informed pedagogy, health, and gender equity / Tasha Golden -- "Can a poem stop a jail from being built?" : on fugitive counterethics as prison pedagogy / Meghan G. McDowell and Alison Reed -- Organized prison writing -- Writing, bodies, and performance : cultural resistance behind prison walls / Julie Rada and Rivka Rocchio -- The Arthur kill alliance : prison newspapers and writing education / Laura Rogers -- Prison writing instruction and the American prison writing archive / Sean Moxley-Kelly -- Writing-about-writing pedagogies in prison / Kimberley Benedict -- Contributors -- Index